2022
DOI: 10.1016/j.brs.2022.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Calcium channels control tDCS-induced spontaneous vesicle release from axon terminals

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 58 publications
3
10
1
Order By: Relevance
“…There is no current understanding of how an electrical current induces such metabolic effects. However, we also observed the effects of tDCS on calcium-related pathways, which coincides with previous studies by us and others [79,80,[85][86][87]. Calcium is known to modulate mitochondrial functioning [88][89][90], affecting ATP production [90] and regulating oxidative stress [91,92].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There is no current understanding of how an electrical current induces such metabolic effects. However, we also observed the effects of tDCS on calcium-related pathways, which coincides with previous studies by us and others [79,80,[85][86][87]. Calcium is known to modulate mitochondrial functioning [88][89][90], affecting ATP production [90] and regulating oxidative stress [91,92].…”
Section: Discussionsupporting
confidence: 92%
“…Given multiple hints that calcium signaling is involved in energy production processes that are affected by tDCS and given our previous study showing that tDCS modulates calcium dynamics [79,80], we investigated whether calcium-related genes were also altered by tDCS. We found that, as a whole, calcium-related genes are significantly affected by tDCS (Figure 9a).…”
Section: Discussionmentioning
confidence: 99%
“…However, experimental data from recorded from axons show that polarization is higher than the theoretical predictions [14,15]. This disparity is due to the active involvement of ionic channels during the polarization process, such as the sodium channels and calcium channels, which were also shown to affect axonal polarization and synaptic vesicle release [15,39]. In the herein study, we demonstrate that along with the sodium channels and calcium channels, potassium channels also play a vital role in the modulation of synaptic vesicle release by DCS.…”
Section: Discussionmentioning
confidence: 98%
“…Ionic channel dynamics determines and regulates the waveform of the AP and a small variation in the axonal ionic channel dynamic can alter the AP morphology. Nonetheless, it is well established that the axon terminals are the most sensitive subcellular compartment to external electrical field application both by passive polarization in accordance with the cable equation [11,12,14,15], and by active involvement of ionic channels, which further enhances the polarization of the axon terminals [14,15,39]. Interestingly, the same ionic channels dynamics determine the initiation, waveform, and propagation of the APs [24,59].…”
Section: Discussionmentioning
confidence: 99%
“…Experiments in cortical and hippocampal slices found evidence of acute changes in synaptic efficacy that are strongest with E-field aligned with the activated axonal inputs [13,25]. Using slices from motor cortex, Vasu and Kaphzan reported changes in the rate of spontaneous vesicle release by dc stimulation, dependent on voltage-gated sodium, potassium, and calcium channels [61][62][63], suggesting modulation of presynaptic release machinery. However, electrophysiological measures of synaptic transmission include the influence of postsynaptic mechanisms, and the effects of dc stimulation on action potential-evoked presynaptic release have yet to be measured.…”
Section: Presynaptic Mechanismsmentioning
confidence: 99%